Biofortificação simultânea com selênio e zinco: interação iônica e produção do arroz - Borghi, Edinei José Armani (2022)
Selenium (Se) and zinc (Zn) are essential elements for humans and animals. The understanding of ionic interactions is a key factor to carry out the nutritional management of crops in a balanced way. The aim of this study was to evaluate possible interactions between Se and Zn in rice, as well as the implications of simultaneous supply of Se and Zn on rice growth, yield and biofortification. The experiment was carried out in a completely randomized design, in a 2x5 factorial scheme, being studied two forms of Se (sodium selenate - Na2SeO4 and sodium selenite - Na2SeO3) at a dose of 0.75 mg dm-3 of Se, combined with five doses of Zn (0, 12, 24, 36, 48 mg dm-3) in the form of Zn sulfate (ZnSO4.7H2O), with five replications. The results obtained showed that there was no interaction between Se and Zn in the rice crop. Rice growth and production did not respond differently to the supply of selenite and selenate. Selenate is more absorbed and accumulated in shoots and rice grains. The supply of 35.03 mg dm−3 of Zn promoted the highest values of production, content and accumulation of Zn in rice grains, as well as an adequate intake of Zn in the diet. The consumption of brown rice grown with 0.75 mg dm-3 of selenite allowed adequate daily intake of Se. The supply of Zn did not affect the levels of N, P, K, Ca, Mg, S, Fe, Mn, Cu and B in the rice grains, while the forms of Se had an effect only on the levels of Fe and Cu in the grains. This study showed that the simultaneous supply of Se (selenite or selenate) and Zn is a promising strategy for rice biofortification with Se and Zn.